Regional initiatives for Japanese entrepreneurs : a study on the Tokyo metropolis area - Nguyen, Nga (My University, 2019)
Private businesses have a crucial part in the prosperity or failure of an economy. It is, therefore, the government’s top priority to provide support, both financially and politically, to help its businesses thrive in its economic conditions. This study aims to explore the characteristics of regional government subsidized programs designed for this purpose, in particular, the Tokyo Metropolitan Government (TMG)’s initiatives, and reveal their impact on local entrepreneurs. The study combined semi-structured interviews and public resources from the Japanese government to facilitate a qualitative analysis. Participants include eight entrepreneurs either currently running a business or aspiring to have one. The semi-structured interview model allows a certain degree of flexibility to adapt the interview content to the respondents’ specific situations. This provides the proper framework to extract the information on their opinions regarding the TMG initiatives, both personally and professionally. The data collected from these interviews was then analyzed in contention with other statistics published by the Tokyo local authorities to identify these entrepreneurs’ awareness and attitudes towards the TMG’s initiatives. The study found there is a hesitation to utilize the services and programs provided by the TMG due to several factors including bias and perceptions of the entrepreneurs about bureaucracy as well as ethical issues. The thoroughness of the findings, however, provides a solid framework for further studies to be conducted in this field.